SISTEM REKRUTMEN TENAGA PENDIDIK DI PERGURUAN TINGGI STAI MA’ARIF KALIREJO KABUPATEN LAMPUNG TENGAH LAMPUNG TAHUN 2022 - Muhamad Asror (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2022)
This study aims to determine the strategy of the recruitment system for educators and education personnel. This research was conducted at the STAI Ma'arif Kalirejo College, Central Lampung Regency, Lampung Province and was carried out in June-October 2022. In this study, a qualitative approach was used, with descriptive qualitative methods. The respondents were the head of STAI Ma'arif Kalirejo, lecturers, and administrative staff in the campus environment as well as cleaning and security personnel. Data collection techniques used are interview, observation, and documentation studies. After the data is collected, data processing is carried out by analyzing the existing data, and then interpreting it with reference to the research framework. The results of this study indicate that the recruitment strategy carried out by the head of STAI Ma'arif Kalirejo is quite good. This recruitment activity begins by analyzing the needs of existing educators and education staff and the state of the number of students in each study program in the current year and estimates for the following year until the placement of new lecturers and employees. The method used can be said to be quite effective for the institution, this is proven by the absence of lecturers or educators who are absent from work, as stated by the head of STAI Ma'arif Kalirejo as the implementer and decision maker in the recruitment of educators and staff. education at STAI Ma'arif Kalirejo, Central Lampung Regency, Lampung Province. For the sake of improvement in the future, the author suggests that the recruitment of educators and educational staff in higher education should be carried out more objectively, the quality of the selection of new lecturers and employees should also be improved and recruitment activities should be carefully designed in order to meet the needs of the institution to the fullest and according to educational goals.